Memories of the Light: Evanescent Visibility and Political Spectrum Listening on Otra vez Marcelo (2005) by Teatro de los Andes (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This work is interested in thinking about the relationship between recent past, aesthetic experience, theater and scenic corporalities, focusing on the representation of violence and drama of those who disappeared during Latin American genocidal dictatorships. For this, the Bolivian case is reviewed through the staging of Otra vez Marcelo (César Brie, 2005) by Teatro de los Andes (TA), whose centerpiece is the topic of shared memory, understood as a problematic exercise of review of the past and dispute for the emergence of “another political history” previously silenced. Marcelo Quiroga Santa Cruz, who was murdered in July 1980 and remains missing, is the protagonist of a play that searches for the public “reappearance” of his intellectual figure and ethical and militant legacy.
Keywords: Bolivia; Memory; Theatre; Politics.